2022
DOI: 10.1007/s11270-021-05496-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Ecotoxicity of Pollution by Potentially Toxic Elements by Biological Indicators of Haplic Chernozem of Southern Russia (Rostov region)

Abstract: The content of various chemical elements such as metals, metalloids, and nonmetals in the environment is associated with natural and anthropogenic sources. It is necessary to normalize the content of metals, metalloids, and nonmetals as potentially toxic elements (PTE) in the Haplic Chernozem. The soils of the Southern Russia are of high quality and fertility. However, this type of soil, like Haplic Chernozem, is subject to contamination with a wide range of PTE. The aim of the work was to rank metals, metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Soil Quality Standards of Turkiye (SQST) set the maximum allowable limits for cobalt, thallium, and uranium as 20 mg/kg, 5 mg/kg, and 1 mg/kg respectively [31]. Maximum permissible concentrations in soils [8] for Ag, Bi, Sb, Th, and V are 3.1 mg/kg, 6.6 mg/kg, 3.2 mg/kg, 28.5 mg/kg, and 296 mg/kg respectively. This study shows the mean concentration values of Co exceed the SQST's limit, however, Ag, Bi, Sb, Th, Tl, U, and V values appear to be in a normal range.…”
Section: Concentrations Of Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil Quality Standards of Turkiye (SQST) set the maximum allowable limits for cobalt, thallium, and uranium as 20 mg/kg, 5 mg/kg, and 1 mg/kg respectively [31]. Maximum permissible concentrations in soils [8] for Ag, Bi, Sb, Th, and V are 3.1 mg/kg, 6.6 mg/kg, 3.2 mg/kg, 28.5 mg/kg, and 296 mg/kg respectively. This study shows the mean concentration values of Co exceed the SQST's limit, however, Ag, Bi, Sb, Th, Tl, U, and V values appear to be in a normal range.…”
Section: Concentrations Of Heavy Metalsmentioning
confidence: 99%
“…Environmental pollution caused by the accumulation of common heavy metals (As, Al, Cd, Cr, Cu, Hg, Pb, Ni, and Zn) and their anthropogenic sources in soils has been extensively studied before. However, the ecotoxicity of uncommon heavy metals (Ag, Bi, Co, Sb, Th, Tl, U, and V) in soils is currently underestimated and needs to be researched in order to better understand their impact on the environment [8]. This is due to the fact that their pollution is far less prevalent than that of common heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…1 Residual dyes and waste in industrial effluent discharge are a major contributor to water pollution due to their highly toxic and hazardous nature even at low concentrations. 2,3 More seriously, most organic dyes are resistant to aerobic digestion, recalcitrant, 4 and stable toward oxidizing agents, 5 which create serious threats to human health, including carcinogenic 6 and mutagenic effects. 7 From an environmental view, they can potentially damage aquatic biota by blocking natural sunlight and can dissolve oxygen in water bodies due to their complex chemical nature.…”
Section: Introductionmentioning
confidence: 99%
“…Filella et al [3] reported an ordering for antimony species toxicity, which is antimonites (Sb 3+ ) > antimonates (Sb 5+ ) > organoantimonials. Kolesnikov et al [6] evaluated the ecotoxicity of 23 metals, metalloids, and nonmetals in a Haplic Chernozem and proposed three hazard classes with Sb in class II (intermediate hazard class). Antimony was determined to be bound to relatively immobile Fe and Al oxihydroxides and to a lesser degree as antimony-organic substances [7].…”
Section: Introduction To Antimonymentioning
confidence: 99%